Evaluation of Measured Digital Output of Gas Sensors During Spontaneous Heating of Coal. Issue 6 (2nd November 2019) - Kumar, Subhash; Mishra, P. K.; Kumar, Jitendra
ABSTRACT: Spontaneous heating is the major cause of unintentional coal burning in the underground coal mine. It is responsible for releasing a number of combustible gases. For measuring the concentration of these gases, the role of gas sensors becomes very important to plan efficient preventive measures. In general, the outputs of sensor produced in digital format after processing through the microcontroller platform. However, the sensor data need to be displayed in a standard format. Therefore, a tool is needed to convert the digital output of the sensors to the standard format (PPM or %) in actual environmental condition. Hence, in the present paper, mathematical expressions have been deduced for each sensor to produce the output in a standard format for test environmental condition and the same were compared simultaneously with the handheld gas analyzer. The results were found in agreement.